Challenges and Strategies for Fulfilling Specialist and Subspecialist Doctors for Improvement Service Hospital Referral: Systematic Literature Review - Evalindo Hutabarat; Amal Chalik Sjaaf (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The availability of specialist and subspecialist doctors in sufficient numbers and with appropriate competencies is an absolute prerequisite for the success of the transformation of referral services. Data from the Ministry of Health in 2024 shows that Indonesia only has 0.18 specialist doctors per 1,000 population spread across various health facilities. This figure is still far below the ideal target of 0.28 per 1,000 population, so an additional 29,179 specialist doctors are needed. Objective: This research aims to identify obstacles that hinder availability doctor specialists and subspecialists at the hospitals, as well as to explore effective approaches to overcome these problems. Method: This study uses the Systematic Literature Review method. The method of selecting articles in this study is to search for articles that meet the inclusion and exclusion criteria through the Google Scholar database with the keywords